การวิเคราะห์กระบวนการผลิตสีของเครื่องพิมพ์ 3 มิติ ระบบเอฟดีเอ็ม - สิรภัทร ทิตาสิริมณีรดา (จุฬาลงกรณ์มหาวิทยาลัย, 2020)
This project aims to analyze color production process of a 3D printer with 3D printing technology, together with inkjet color printing on the surface of objects. The effect of thickness on printed colors is also studied. Two patterns (Texture and Surface) of color charts were printed to determine the print format to be used in the experiments. The Surface pattern was selected. A 49-color chart was printed with 5 different thicknesses: 1, 2, 4, 8 and 16 mm, where each square had a different color. It was created to study the influence of thickness on printed colors. A test chart of 125 squares with the thickness of 4 mm was created. The colors in each square were generated by dividing the RGB values (from 0 to 255) into 5 equal intervals, and all possible combinations of these values resulted in a total of 125 different colors. The printed color charts were measured in terms of L*a*b* (D65/2°) values. The measured values were compared to the originals (converted from sRGB). The 49-color chart was used to analyze the effect of thickness. The distributions of 125 colors were compared between the prints (measured values) and the originals (converted from sRGB). It was found that thickness had no obvious effect on the printed colors. In addition, the color ranges generated by the printing inks and the calculations of the printing ink proportions affected the colors printed with the 3D printer.